Rancang Bangun Robot Vacum Cleaner Berbasis Mikrokontroler dengan Pengendali Smartphone Android - Ade Zulkarnain Hasibuan; Munjiat Setiani Asih (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2019)
Robots are electro mechanical equipment which currently greatly helps human work. On a household scale robots that are often used are dust cleaning robots, it's just that to get this robot people have to spend not a little money. By utilizing a microcontroller with the Arduino platform, dust cleaning robots can be made that have a more affordable price and have reliable features. By using Arduino, a robot can be made that can clean the dust automatically, which the robot will not hit the wall, besides the robot is also equipped with two brooms on the bottom. A broom intended to clean the dust on the floor and the dust will be sucked by a vacuum fan installed in the lower robot. In addition, the robot can also be used manually using an Android smartphone so that users can easily connect robots to areas that might not have been passed by a robot.